Biological and Molecular Characterization of the Postinvasion Immature Stages of Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) - Da Silva, Ivana Fernandes [UNESP]; Baldin, Edson Luiz Lopes [UNESP]; Specht, Alexandre; Sosa-Gómez, Daniel Ricardo; Roque-Specht, Vânia Ferreira; Morando, Rafaela [UNESP]; De Paula-Moraes, Silvana Vieira (De Gruyter, 2018)
We performed molecular and biological characterizations of immature stages of Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) using insects from different states in Brazil, and different host plants. Three laboratory colonies of H. armigera were established with insects from the states of São Paulo, Bahia, and Distrito Federal, that were collected from citrus, cotton, and corn, respectively. For each colony, microsatellites were used to assess genetic similarity among insects. The biology of the immature stages from each colony also was compared under laboratory conditions (25 ± 1 °C, 70 ± 10% RH, 14:10 h [L:D] photoperiod). Microsatellite analysis revealed genetic variability in sampled specimens and that the grouping of individuals was independent of the geographic origin. The utility of an artificial diet was validated during the comparative biology experiment, and the ingredients of the artificial diet were analyzed for purity, particle size, and the presence and quantity of aggregates. The mean development times of the larvae and pre-pupae from the 3 locations were similar, and mean total development time (egg to adult) was not significantly different.
Keywords: Artificial diet; larval development; molecular characterization; old world bollworm; standardization of breeding